Application of central composite design to optimization of Yellow Tartarazine and Methylene Blue environmentally clean adsorption by untreated walnut shells - Mahmoud Trachi; Moussa Abbas; Mohamed Trari (Adsorption Science & Technology)
Climate change poses a real threat to the water security by altering the precipitation patterns and other weather variables, desirability function (df) was used to determine the interactive effects and optimize with the Central Composite Design (CCD) of important variables such as initial dyes concentration (C o : 20–100 mg L –1 ), solution pH (1.5–11), temperature (20–60 °C) and adsorbent dosage (0.1–1.3 g L –1 ) for the removal of toxic Yellow Tartarazine (YT) and Methylene Blue (MB) onto Untreated Walnut Shells (UWS). The analysis of variance (ANOVA) was applied for the treatment of experimental data, fitted by a second-order polynomial equation and multiple regression analysis. The ideal conditions optimized according to the response surfaces are initial concentration (C Oyt  = 60 mg L –1 , pH YT  = 1.5, D YT  = 0.7 g L –1 and T YT  = 40 °C for YT and (C o MB  = 60 mL –1 , pH MB  = 8.5, D MB = 0.7 g L –1 and T MB  = 40 °C for MB). Experimental confirmation allowed to accurately determine the maximum eliminations (76.15) for YT and (76.81%) for MB under optimal conditions. Several error analysis equations were used to measure the goodness of fit. Kinetic studies showed that the adsorption kinetic data are well modeled by a pseudo-second-order model. Among the different models used to fit the experimental isotherms, the Langmuir model gave the best correlation with capacities q max of 55.55 and 50.00 mg/g, for YT and MB respectively at 40  o C. The effect of temperature on the adsorption isotherms allowed to arrive at the thermodynamic functions, the negative values of free energy ( ΔG° ), enthalpy ( ΔH° ) and entropy ( ΔS° ) indicate a spontaneous and exothermic adsorption of physical nature, confirmed by the activation energy ( E a ) for both dyes. The elimination of pollutants by new-generation adsorbents has proven to be very effective by application of statistical methodology, Central composite design and the desirability function.